2019
DOI: 10.3892/mmr.2019.10542
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‑208a directly targets Src kinase signaling inhibitor 1 to facilitate cell proliferation and invasion in non‑small cell lung cancer

Abstract: The abnormal expression of microRNAs (miRNAs/miRs) has a critical function in the formation and progression of non-small cell lung cancer (NSCLC). Therefore, understanding the association between NSCLC and dysregulated miRNAs may allow for the identification of novel diagnostic and therapeutic biomarkers for patients with this malignancy. Previous studies have validated miR-208a as a cancer-associated miRNA in multiple different types of human cancer, however, its expression pattern and precise function in NSC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…As summarized in Figure 2, the possible mechanisms through which miR‐208a promotes tumorigenesis and the proliferation and invasion of tumor cells include the following: (1) direct repression of the tumor‐suppressor gene encoding AT‐rich interactive domain‐containing protein 2 (ARID2) 26 ; (2) direct repression of the SOX6 protein, which results in downregulation of p21, 28,30 upregulation of cyclin D1, and phosphorylation of Rb, 28 thereby promoting cell cycle progression 28,30 ; (3) direct targeting of p21 with corresponding activation of the AKT/mammalian target of rapamycin (mTOR) pathway 30 ; (4) targeting of secreted frizzled‐related protein (SFRP1), a tumor‐suppressor protein that inhibits the WNT signaling pathway, as well as negative regulation of maternally expressed gene 3 (MEG3), a tumor‐suppressor gene 27 ; (5) activation of the extracellular signal‐regulated 1/2 pathway via programmed cell death protein 4 (PDCD4), a tumor suppressor 97 ; (6) direct targeting of Src kinase signaling inhibitor 1 (SRCIN1), which has inhibitory effects on tumorigenesis and tumor development 98 ; and (7) increasing the number and self‐renewal of stem cells through the miR‐208a /SOX2/β‐catenin/LIN28/ let‐7a /DICER1 regulatory feedback loop 99 . In addition, overexpression of miR‐208a suppresses the apoptosis of cancer cells by direct targeting of apoptosis‐related genes 29,30,100 …”
Section: Mir‐208a In Cancer Biologymentioning
confidence: 99%
See 1 more Smart Citation
“…As summarized in Figure 2, the possible mechanisms through which miR‐208a promotes tumorigenesis and the proliferation and invasion of tumor cells include the following: (1) direct repression of the tumor‐suppressor gene encoding AT‐rich interactive domain‐containing protein 2 (ARID2) 26 ; (2) direct repression of the SOX6 protein, which results in downregulation of p21, 28,30 upregulation of cyclin D1, and phosphorylation of Rb, 28 thereby promoting cell cycle progression 28,30 ; (3) direct targeting of p21 with corresponding activation of the AKT/mammalian target of rapamycin (mTOR) pathway 30 ; (4) targeting of secreted frizzled‐related protein (SFRP1), a tumor‐suppressor protein that inhibits the WNT signaling pathway, as well as negative regulation of maternally expressed gene 3 (MEG3), a tumor‐suppressor gene 27 ; (5) activation of the extracellular signal‐regulated 1/2 pathway via programmed cell death protein 4 (PDCD4), a tumor suppressor 97 ; (6) direct targeting of Src kinase signaling inhibitor 1 (SRCIN1), which has inhibitory effects on tumorigenesis and tumor development 98 ; and (7) increasing the number and self‐renewal of stem cells through the miR‐208a /SOX2/β‐catenin/LIN28/ let‐7a /DICER1 regulatory feedback loop 99 . In addition, overexpression of miR‐208a suppresses the apoptosis of cancer cells by direct targeting of apoptosis‐related genes 29,30,100 …”
Section: Mir‐208a In Cancer Biologymentioning
confidence: 99%
“…Furthermore, overexpression of miR‐208a decreases E‐cadherin expression (an epithelial cell marker) and increases the levels of fibronectin and vimentin (interstitial cell markers), leading to the epithelial‐to‐mesenchymal transition, which is an initial step in tumor metastasis 25 . Clinical studies have demonstrated that overexpression of miR‐208a is associated with lymph node metastasis and TNM stage in patients with gastric cancer 27 and lung cancer 98 . In addition, a Kaplan‐Meier analysis of patients with gastric cancer revealed that patients with higher miR‐208a expression levels had a significantly shorter overall survival time 27 …”
Section: Mir‐208a In Cancer Biologymentioning
confidence: 99%
“…MiR-208 was described to promote cell proliferation in human esophageal squamous cell carcinoma [ 56 ], promote EMT in pancreatic cancer cells [ 57 ], stimulate tumorigenesis in colorectal cancer [ 58 ], suppress cell apoptosis in gastric cancer [ 59 ], or to facilitate cell proliferation and invasion in non-small cell lung cancer and in hepatocellular carcinoma [ 54 , 60 ]. In 2015, miR-208-3p was found to be transcriptionally regulated by TGFß1 and to directly target ARID2 [ 54 ].…”
Section: Arid2 In Hepatocellular Carcinoma (Hcc)mentioning
confidence: 99%
“…Recently, several papers have shown that p140Cap can be targeted by a variety of miRNAs in different types of tumors such as lung, pancreatic, gastric, breast, ovarian and colorectal cancer as well hepatocellular and cervical carcinomas (Table 1). In almost all the cases, the direct targeting of p140Cap has been validated in cancer cell lines and the resulting downregulation of p140Cap expression promotes tumor features such as proliferation [56][57][58][59][60][61][62][63][64][65][66][67][68], migration [56,58,60,61,63,67,68], invasion [60,64] and angiogenesis [69]. Among the reported miRNAs, miR-150 has been described as a negative regulator of p140Cap in multiple malignancies such as BC, where it promotes migration, invasion and expression of EMT markers in cancer cells [70].…”
Section: Gene Status and Regulation Of Expression Of Srcin1 In Cancermentioning
confidence: 99%